Structural Damage Assessment and Seismic Performance Optimization (case study: Ambon City Regional Representative Council Building) - Madobaafu, Sarivanoly; Wibowo, Ari; Wisnumurti (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
The earthquake in Ambon City in 2019 damaged several buildings, including the DPRD building. This study aims to evaluate the seismic performance of the building and identify effective structural strengthening methods. The method used is pushover analysis, with structural modeling carried out using SAP2000 v.26. Lateral loads are applied gradually until the structure collapses. Secondary data in technical drawings and building documentation are used to build a structural model in SAP2000. The analysis results show that before reinforcement, the maximum roof displacement (?) reached 0.352 meters, with a total building height of 17 meters, resulting in a drift ratio of 0.0207 in the X–X direction, which is assumed to be the weak axis. Based on the ATC-40 criteria, this condition indicates the structural performance level in the